Study and Analysis on Biometrics and Face Recognition Methods - Singha, Anjani Kumar; Singla, Anshu; pandey, Rajneesh kumar (IJRDO -Journal of Computer Science Engineering, 2016)
— Human Biometrics is a rising technology, which has been broadly used in forensics, safe access and top-security prison. A biometric system is primarily a pattern recognition system that recognizes a person by determining the verification by using his different biological features i.e. Fingerprint, retinascan, iris scan, hand geometry, and face recognition are important physiological biometrics and behavioral trait are Voice recognition, keystroke-scan, and signature-scan. In this paper different biometrics techniques such as Iris scan, retina scan and face recognition techniques are discussed.